When Low Leisure-Time Physical Activity Meets Unsatisfied Psychological Needs: Insights From a Stress-Buffer Perspective - Gerber, Markus; Isoard-Gautheur, Sandrine; Schilling, René; Ludyga, Sebastian; Brand, Serge; Colledge, Flora (Frontiers in Psychology, 2018)
Background: Few studies have tested whether the stress-buffering effects of leisure-time physical activity (LTPA) depend on other resources, such as the satisfaction of basic psychological needs. Therefore, the present study examines the interaction between perceived stress, LTPA and psychological need satisfaction (PNS) on occupational burnout symptoms in a sample of Swiss workers. Methods: The sample consisted of 306 employees (48% women; Mage=42.9 years, SD=14.1). Perceived stress was assessed with the Perceived Stress Scale, LTPA with the International Physical Activity Questionnaire, PNS (autonomy, relatedness, competence) with the Need Satisfaction Scale, and occupational burnout symptoms with the Shirom-Melamed Burnout Measure. A hierarchical regression analysis and single slopes tests were performed to examine 2-way and 3-way interactions. Results: Stress was positively correlated with burnout, and negatively correlated with LTPA and PNS levels. LTPA was positively associated with PNS, and negatively correlated with burnout. A negative association existed between PNS and burnout. In the hierarchical regression analysis, all main effects, 2-way and 3-way interactions were significant. People who engaged in more LTPA reported fewer burnout symptoms, if they reported high stress. However, the potential of LTPA to buffer stress was particularly evident in participants who reported low PNS. Conclusions: If adult workers are exposed to elevated stress, they are particularly likely to show increased burnout levels if they report low LTPA in combination with low PNS, specifically a lack of autonomy, competence and relatedness.